Preparation and characterization of naphthoquinone derivatives and isomers / Malinda Anfa Anwar - Anwar, Malinda Anfa (2007)
Naphthoquinone and its derivatives were found to have good antimicrobial and other biological activities. In this study, bromobenzene as ‘R‘group was used to attach to the bromoketone. The bromoketone (2,4-dibromoacetophenoe) was treated with pyridine to form pyridinium salts. The percentage yield of pyridinium salts obtained was 66.38%. Substituted quinone, compound 33 was obtained by reacting 2-methyl-1,4 naphtoquinone or menadione with pyridinium salts and percentage yield obtained was 82.219%. This compound 33 gave two colors, red compound and yellow compound.Mixture of both compounds gave same results from NMR and IR analysis from previous study compared to NMR and IR analysis of pure yellow compound obtained. The problem is only the pure yellow compound was obtained whereas the red compound cannot be purified due to the time constraint. The possible stereoisomers for compound 33 based on the mechanism of reaction, as the product structure shown below.